2023
DOI: 10.1007/s00127-023-02523-y
|View full text |Cite
|
Sign up to set email alerts
|

The association of sociodemographic characteristics with work disability trajectories during and following long-term psychotherapy: a longitudinal register study

Abstract: Purpose This register-based study examined the trajectories of depression or anxiety disorder-related work disability during and following long-term psychotherapy and identified sociodemographic factors that indicate membership in different trajectory groups. Methods Data were drawn from national registers (Statistics Finland, Social Insurance Institution of Finland). Participants included a random sample of Finnish working-age individuals (18–55 years) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…15 A recent study on disability trajectories of rehabilitative psychotherapy recipients also found that manual workers who received therapy were more likely to remain on the path of prolonged disability than non-manual employees who received similar therapy. 16 In future studies we should, however, pay more attention to gender and also explicitly test the possibly cumulative effects of occupational grade and gender on gains from psychotherapy. For doing this, we need to move beyond the logic of conventional net effect analyses which estimate the isolated impact of individual variables on treatment outcomes, and instead focus on the effects of different occupational grade-gender configurations by using for example fuzzy-set analysis.…”
Section: Discussionmentioning
confidence: 99%
“…15 A recent study on disability trajectories of rehabilitative psychotherapy recipients also found that manual workers who received therapy were more likely to remain on the path of prolonged disability than non-manual employees who received similar therapy. 16 In future studies we should, however, pay more attention to gender and also explicitly test the possibly cumulative effects of occupational grade and gender on gains from psychotherapy. For doing this, we need to move beyond the logic of conventional net effect analyses which estimate the isolated impact of individual variables on treatment outcomes, and instead focus on the effects of different occupational grade-gender configurations by using for example fuzzy-set analysis.…”
Section: Discussionmentioning
confidence: 99%